Pengaruh Motivasi, Prestasi Belajar, dan Ekspektasi Kerja Terhadap Minat Mahasiswa Akuntansi Untuk Melanjutkan Studi Magister Akuntansi - Amalia Belladina; Junaidi Junaidi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
This study discusses The Influence of Motivation, Learning Achievement, and Job Expectation on The Interest of Accounting Students to Continue the Study of Masters in Accounting. This type of research is quantitative. The data collection method used is primary data by giving questionnaires to accounting students at the Islamic University of Malang, Maulana Malik Ibrahim State Islamic University of Malang, and the State University of Malang. The sampling used purposive sampling technique which resulted in a sample of 188 respondents. The analysis technique used is multiple linear regression analysis. The results showed that the variable of Motivation, Learning Achievement, and Job Expectation had a simultaneous and partial effect on The Interest in Continuing Masters Studies. Keywords: motivation, Learning Achievement, Job Expectation, Interest in Continuing Masters Studies.